2015
DOI: 10.3892/mmr.2015.4534
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of lycopene pretreatment on transient global cerebral ischemia-reperfusion in rats: The role of the Nrf2/HO-1 signaling pathway

Abstract: Abstract. The present study aimed to investigate the neuroprotective effect of lycopene in a mouse model of bilateral common carotid artery occlusion (BCCAO) and the role of the Nrf2/HO-1 signaling pathway. A total of 60 male C57BL/6 mice, aged 12 weeks and weighing 20-24 g, were used in the present study. The mice were randomly assigned to three groups: Control, BCCAO and BCCAO + lycopene. The neurological score was assessed 24, 48 or 72 h following BCCAO. Hematoxylin and eosin staining, and terminal deoxynuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 42 publications
3
34
0
1
Order By: Relevance
“…HO1, which has the ability of conversing heme into biliverdin, is one of the key phase II enzymes maintaining intracellular redox homeostasis by neutralizing oxidative stress. 36 As a detoxifiying enzyme, NQO1 catalyzes the 2-electron reductive metabolism and detoxification of quinies, protecting cells from oxidative stress-induced injury. 37 Indeed, in the current study, the Nrf2 nuclear translocation was found to be inhibited in AGEs-exposed aorta.…”
Section: Discussionmentioning
confidence: 99%
“…HO1, which has the ability of conversing heme into biliverdin, is one of the key phase II enzymes maintaining intracellular redox homeostasis by neutralizing oxidative stress. 36 As a detoxifiying enzyme, NQO1 catalyzes the 2-electron reductive metabolism and detoxification of quinies, protecting cells from oxidative stress-induced injury. 37 Indeed, in the current study, the Nrf2 nuclear translocation was found to be inhibited in AGEs-exposed aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a crucial modulator of HO-1 expression [26]. Nrf2/HO-1 signaling is a vital path in the apoptosis process [27]. HO-1 is a stress-responsive enzyme that produces antioxidants, anti-inflammatory agents, and regulators of apoptosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that Nrf2 plays an important role in modulating acute inflammatory responses. Under basal conditions, Nrf2 is located in cytoplasm and is bound to its inhibitor, Kelch-like ECH associated protein 1 (Keap1), which is associated with the actin cytoskeleton and prevents Nrf2 from entering the nucleus [11,12,13]. Under oxidative or xenobiotic stress conditions, Nrf2 translocates from the cytoplasm to the nucleus, resulting in a cytoprotective response which is characterized by the upregulation of a group of antioxidant enzymes and decreased sensitivity to oxidative damage.…”
Section: Introductionmentioning
confidence: 99%